College Students' Developing Understanding of Moral Expertise: A Longitudinal Case Study of the Importance of Models, Mentors, and Practice. Issue 4 (2nd October 2022) - Cox, Samuel J. E.; Waldbillig, Luke T.; Glanzer, Perry L.
Abstract: Higher education scholars have varied views about the importance of moral experts for college students. To complicate matters, higher education scholars and student affairs professionals often have little knowledge of students' perspectives regarding such questions. This article provides a longitudinal case study analysis of students at a mid-size, faith-based research university, exploring how students seek moral expertise through social support from members of their social or religious communities. We interviewed fourteen students in their first and third years of enrollment regarding their understanding of moral expertise. Findings suggest students sought out moral experts with religious organizations and peer mentors providing the primary sources of moral expertise.